Rape in Armed Conflicts in the Democratic Republic of Congo: A Systematic Review of the Scientific Literature - Mpinga, Emmanuel Kabengele; Koya, Mapendo; Hasselgard-Rowe, Jennifer; Jeannot, Emilien; Rehani, Sylvie B.; Chastonay, Philippe (Trauma, violence & abuse, 2017)
We conducted a systematic review of the scientific literature between 1996 and 2013 on rape in war-ridden Eastern Democratic Republic of Congo (DRC) in order to better understand the interest of the scientific community in describing the magnitude and characteristics of the problem. The literature search was conducted in French and English using several databases (Pubmed, PsycInfo, Sapphire, BDSP, Embase, Rero, and Web of Science) with the key words “rape and DRC” combined with several Medical Subject Headings concepts. Our systematic review yielded 2,087 references, among which only 27 are original studies, that is 20 are based on population surveys and the remaining 7 are original data based on case studies and reviews. Ten studies provided prevalence rates of rape victims, 18 provided specific information on the profile of the victims, 10 reported that most of the perpetrators of rape were military personnel, 14 referred to the negligence of the government in protecting victims, and 10 reported a lack of competent health-care facilities. The awareness of rape in conflict-ridden DRC is still limited as reported in the scientific literature: Published scientific papers are scarce. Yet more research would probably help mobilize local authorities and the international community against this basic human rights violation.